The healer power of the speech from Hippocrates to Clement of Alexandria (Circe de clásicos y modernos, 2018)
Clement of Alexandria presents the Lοgosof God as a physician able to heal by means of his word the passions of the new believer while he is guided and instructed in the duties of Christian life. The principles developed by the Pedagogus, though they instantiate the ideology of a philosophy that struggles to set up its power in a definitive way, also attest the influ-ence from earlier authors, among which Hippocrates, Plato, Philo of Alexandria and the New Testament documents represent the textual parnassus with indisputable predominance in the Alexandrian theologian’ thought. In spite of the chronological distance that separates Clement from these authors, it is remarkable how the medical criterion stopped from being a simple element of the sophists’ rhetorical discourse to give way to Hippocrates’ professional practice and acquire a philosophical status in the works of Plato, Philo and, later, in the New Testament’s speech. In this sense, a review of these writers will allow us to confirm their influence on Clement as well as their functionality inside the Christian discourse of 2nd century.
Keywords: Logos; Pedagogus; physician; word; healing